Crisis and Emergency Risk Messaging in Mass Media News Stories: Is the Public Getting the Information They Need to Protect Their Health?. Issue 10 (2nd October 2016) - Parmer, John; Baur, Cynthia; Eroglu, Dogan; Lubell, Keri; Prue, Christine; Reynolds, Barbara; Weaver, James
ABSTRACT: The mass media provide an important channel for delivering crisis and emergency risk information to the public. We conducted a content analysis of 369 newspaper and television broadcast stories covering natural disaster and foodborne outbreak events and coded for seven best practices in crisis and emergency risk messaging. On average, slightly less than two (1.86) of the seven best practices were included in each story. The proportion of stories including individual best practices ranged from 4.6% for "expressing empathy" to 83.7% for "explaining what is known" about the event's impact to human health. Each of the other five best practices appeared in less than 25% of stories. These results suggest much of the risk messaging the public receives via mass media does not follow best practices for effective crisis and emergency communication, potentially compromising public understanding and actions in response to events.